The Internal Factors Affecting the Ability of the Organizations to Retain the Customers - Alhasseen, Imad Eldin Mohammed; Algzoly, Fatima Siragalden (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to identify the internal factors affecting the ability of the insurance companies to retain the industrial customer, which provides service, and focused on studying the problem of poor interest in maintaining long-term clients which consider as an importance for company life. The study used the analytical descriptive approach as one of the appropriate methods for this type of research. The data were collected from a selected sample of the clients of the industrial insurance companies in the state of the Red Sea with a total of 100 companies and organizations benefiting from the insurance services. The study reached a number of results, the most important of which is the presence of an impact on the factors (satisfaction of customer needs, customer confidence in service, service delivery method) on the ability to retain customers. The study recommended a number of recommendations related to the results.